A very high prevalence of hepatitis C virus infection among patients undergoing hemodialysis in Kosovo: a nationwide study - Xhevat Jakupi (BMC Nephrology, 2018)
Abstract Background Patients on hemodialysis are at high risk for hepatitis C virus (HCV) infection if measures for effective control of HCV infection in the hemodialysis environment are not implemented. Whereas in developed countries isolated small-scale outbreaks of HCV in hemodialysis units are occasionally reported, HCV transmission in the hemodialysis environment still represents a substantial problem in low-resource countries. This study systematically assessed the prevalence of HCV infection among all patients at all hemodialysis centers in Kosovo, determined the HCV genotype distribution, and reviewed the main risk factors associated with HCV infection in this group of patients. Methods From January to March 2013, blood samples from all patients undergoing hemodialysis at all seven hemodialysis centers in Kosovo were collected. The samples were screened for the presence of anti-HCV antibodies, and seropositive samples were also tested for HCV RNA. Genotyping was performed by sequencing the core region of the HCV genome. Subsequently, face-to-face interviews were conducted with consented patients attending hemodialysis in December 2015 and with the management of all hemodialysis centers in Kosovo. Results The overall seroprevalence of HCV infection among hemodialysis patients in Kosovo was 53.0% (354/668), ranging from 22.3 to 91.1% at different centers. HCV RNA was detected in 323/354 (91.2%) seropositive patients. The most frequent HCV genotype was genotype 1a (62.2%), followed by genotypes 4d (33.1%), 1b (4.0%), and 2c (0.7%). The duration of hemodialysis and receiving dialysis at more than one center were identified as independent significant predictors of anti-HCV positivity. Shortage of staff, lack of resources, and inconsistent use of hygienic precautions and/or isolation strategies were observed. Conclusions The prevalence of HCV infection among hemodialysis patients in Kosovo is extremely high. The relatively low prevalence of HCV infection in the general population, predominance of two otherwise rare HCV genotypes among hemodialysis patients, and longer history of hemodialysis as a predictor of HCV infection all indicate nosocomial transmission due to inappropriate infection control practices as the main transmission route.